Sialidase-like Asp-boxes: sequence-similar structures within different protein folds. - Copley, R; Russell, R; Ponting, C (2001)
Sequence similarity is the most common measure currently used to infer homology between proteins. Typically, homologous protein domains show sequence similarity over their entire lengths. Here we identify Asp box motifs, initially found as repeats in sialidases and neuraminidases, in new structural and sequence contexts. These motifs represent significantly similar sequences, localized to beta hairpins within proteins that are otherwise different in sequence and three-dimensional structure. By performing a combined sequence- and structure-based analysis we detect Asp boxes in more than nine protein families, including bacterial ribonucleases, sulfite oxidases, reelin, netrins, some lipoprotein receptors, and a variety of glycosyl hydrolases. Although the function common to each of these proteins, if any, remains unclear, we discuss possible functions of Asp boxes on the basis of previously determined experimental results and discuss different evolutionary scenarios for the origin of Asp-box containing proteins.